Develop Your Own Florida Olive IPM Plan - Morgan Byron; Eleanor Phillips; Jennifer Lynn Gillett-Kaufman (EDIS)
To remain in optimal health and produce optimal yield, olive trees need excellent nutrition, the right irrigation, and good care to help them stay healthy so that they can withstand injury from pests and diseases. This 10-page fact sheet written by Morgan Byron, Eleanor Phillips, and Jennifer L. Gillett-Kaufman and published by the UF/IFAS Entomology and Nematology Department touches on some aspects of olive tree health that will help improve your trees' natural resistance to pests and pathogens. At the end of the guide is a monthly care and observation schedule to help you recognize when you should begin scouting for key pests and when important grove management decisions should be made. https://edis.ifas.ufl.edu/in1251